Linking the Utilization of Clickbait Headlines and News Marketing Communication Strategy in Online Media - Zinaida, Rahma Santhi; Hardiyanti, Siti Tanti; Amin, Zaid (Universitas Semarang, 2023)
Introduction: The competition in the news industry makes online media portal companies constantly bombard consumers with persuasive news, not a few online media use clickbait on news titles to attract readers to click the news. It turns that, click bait is also linking with the online media marketing communication strategy. The aimed of this research was to know the linking utilization of click bait headline as and marketing communication strategies in tribunsumsel.com. Methods: The method used was a qualitative descriptive method, data collection techniques by observations, interviews and documentations. Key informants are the Company Leader, Online Manager and the Digital Advertising Supervisor in Online Media. Findings: The results of this research was the utilization of Click bait Headlines on tribunsumsel.com portal which become a strategy that being used as an interesting diction chosen to attract visitors and also to accelerate the amount of traffic statistics that had a very significant impact on the amount of advertisement, as one of the income source. Originality: Originality of this research shown by the relational between clickbait headlines and marketing communication strategy which can be both negative and positive. The novelty is where other research about news online portal mostly focuses on news content, journalism etiquette, but this study looks at the other side of clickbait as a new wave phenomenon that online media marketers use to generate revenue. The other point of view from clickbait in Indonesia is interesting to discuss in further research.